Association between Family Support and Dietary Adherence among Diabetes Mellitus Patients at Imelda Indonesian Workers Hospital, Medan - Ali Asman Harahap; Rivaldi Adha; Syahrul Handoko Nainggolan; Yeni Warti; Candra Meriani Damanik (Benih : Journal of Midwifery, 2026)
Introduction: The relationship of family support is closely related to the level of adherence to the diet of people with diabetes mellitus. Family support is the key to successful dietary compliance for people with diabetes mellitus because the family maintains and controls the nutritional intake that must be limited and carried out by sufferers. Purpose: The purpose of this study was to determine the relationship between family support and dietary adherence in adult diabetics at hosfital Imelda Medan. Method: This research method is descriptive with a quantitative approach and a cross sectional research design. Primary data collection was obtained directly through interviews consisting of the identity of the respondent, the characteristics of the respondent (age, gender, education level, type of work, and marital status), as well as the Perceived Dietary Adherence Questionnaire (PDAQ) and Hensarling’s Diabetes Family Support Scale (HDFSS). Data processing uses a computer system and data analysis uses SPSS with a chi-square test. Results: The results showed that there was a relationship between family support and dietary compliance in adults with diabetes mellitus at Hosfital Imelda Medan, which indicated a p-value of 0.001, where the number <α = 0.05. Conclusion: Family support is related to dietary adherence in adults with diabetes mellitus at Hosfital Imelda Medan